الإختلاف و مقارنة المذاهب عن نكاح المتعة عند العلماء الشيعة و أهل السنة - Hermanto, Agus (Universitas Islam Negeri Raden Intan Lampung, 2016)
Abstract: Nikah Mut’ah (Temporary Marriage) in the Views of Sunni and Shi’i Clerics. This article analyses the different views between Sunni and Shi’i Clerics on the legitimacy of Nikah Mut’ah (Temporary Marriage). Even if both the Sunni and Shi’i clerics agree that the marriage practices were permitted by Prophet Muhammad (PBUH) during his lifetime, the two sides disagree whether or not the marriage is still allowed today. The Imami clerics argue that Nikah Mut’ah was legal only in the Prophet era. In their opinions the temporary marriages is allowed in Islam, for those in traveling or in a certain conditions .and the permission is still valid until an unspecified time. The majority of Sunni scholars, however, reject the notions, referring to a hadith that Prophet Muhammad had banned the practices of Mut’ah soon after the Battle of Hunain. الملخص: